2020
DOI: 10.1177/0022042620932289
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions of Harm Reduction and Its Implications for Syringe Exchange Policy

Abstract: In the United States, the rising prevalence of opioid addiction has led to an increase in opioid-related overdose deaths and transmission of infectious disease. This resulted in the declaration of a national public health emergency and the need for harm reduction strategies such as syringe exchange. Florida has seen increases in blood-borne diseases and fatal/nonfatal opioid overdoses, yet harm reduction policy integration has been historically limited. To inform policy change, this study explores the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Despite its proven effectiveness, the acceptability and applicability of HR by health and social services practitioners remain limited, and various factors facilitate or hinder its adoption 21 40–42. MacCoun43 showed that, among practitioners who did not adopt HR, some had based their decision on moral grounds, regardless of its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its proven effectiveness, the acceptability and applicability of HR by health and social services practitioners remain limited, and various factors facilitate or hinder its adoption 21 40–42. MacCoun43 showed that, among practitioners who did not adopt HR, some had based their decision on moral grounds, regardless of its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners may also fear the emergence of legal, social and health problems among their clients 28. Third, its adoption may be limited by contextual barriers, such as lack of funding, stigma that undermines demand for care, resistance from local jurisdictions, and lack of services and trained personnel, particularly in the mental health sector 41. Healthcare providers’ resistance to applying HR in cannabis use leads to limited knowledge and utilisation of effective HR techniques and guidelines among PWUC 5 25.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with local approval and state funding, it may be difficult to sustain local efforts in sparsely populated areas. In rural and suburban locales, it is well known that low community support and community-level stigma further impede harm reduction implementation (Baker, Smith, Gulley, & Tomann, 2020; Ibragimov et al, 2021; Sharp, Barnett, & Vroom, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even with local approval and state funding, it may be difficult to sustain local efforts in sparsely populated areas. In rural and suburban locales, it is well known that low community support and community-level stigma further impede harm reduction implementation (Baker, Smith, Gulley, & Tomann, 2020;Ibragimov et al, 2021;Sharp, Barnett, & Vroom, 2020). Logistic and funding constraints can limit harm reduction services in suburban and rural areas, especially when SSP budgets are based on the number of syringes exchanged (Des Jarlais et al, 2015).…”
Section: Introductionmentioning
confidence: 99%